Isokinetic profile of shoulder internal and external rotators of high school aged baseball pitchers - Mulligan, I. J.; Biddington, W. B.; Barnhart, B. D.; Ellenbecker, T. S. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this descriptive study was to determine whether bilateral differences exist in concentric and eccentric shoulder internal and external rotation strength in high school aged baseball pitchers. Thirty-nine high school aged baseball pitchers were bilaterally tested for concentric and eccentric internal and external rotation muscle performance on a Kin-Com 500-H isokinetic dynamometer at 90°·s-1 and 180°·s-1. Paired t-tests were used to test for differences among extremities, speed, and ratio of external rotation to internal rotation (ER/IR ratios). Concentric peak torque internal rotation at 90°·s-1 was significantly greater (p < 0.05) in the dominant arm compared with the nondominant arm. Statistically significant differences (p < 0.001) were found between the nondominant and dominant in concentric 90°·s-1. The nondominant arm demonstrated significantly greater eccentric strength (p < 0.05) compared with the dominant arm in ER/IR ratios at 90°·s-1 and 180°·s-1. The nondominant arm demonstrated significantly greater eccentric strength (p < 0.05) than the dominant arm in ER/IR ratio at 180°·s-1. Data demonstrated that muscular adaptations are consistent with previous research in this area. Also, muscular adaptations occur in the shoulder in the high school aged population. These data can serve as a guideline to be used by clinicians who rehabilitate shoulders in patients in this population.